Field Responsive Fluids - a Review - (:unkn) unknown (TRANS TECH PUBLICATIONS LTD, 2012)
Magnetorheological (MR), Electrorheological (ER), and Ferrofluids are considered as a class of smart materials due to their novel behavior under an external stimulus such as a magnetic and electrical field. The behavior of these synthetic fluids offer techniques for achieving efficient heat and mass transfer, damping, drag reduction, wetting, fluidization, sealing, and more. Magnetorheological fluids are suspensions of non-colloidal, multi-domain and magnetically soft particles organic and aqueous liquids. Electrorheological fluids are suspensions of electrically polarizable particles dispersed in electrically insulating oil. Ferrofluids are known as magnetic liquids that are colloidal suspensions of ultrafine, single domain magnetic particles in either aqueous or non-aqueous liquids. In this review article a history of these fluids is given, together with a description of their synthesis in terms of stability and redisperibility and how it is understood in various parts of the science and technology. Then the structural changes and Theological properties of these smart fluids under an external stimulus together with a series of applications are presented.
Keywords: Magnetorheological fluids; electrorheological fluids; ferrofluids; MAGNETORHEOLOGICAL FLUIDS; RHEOLOGICAL PROPERTIES; PARTICLE-SIZE; SUSPENSIONS; DISPERSIONS; SILICA; OIL